The Synergetic Effect Induced High Electrochemical Performance of CuO/Cu2O/Cu Nanocomposites as Lithium-Ion Battery Anodes - Wang, Lin-Hui; Gao, Shang; Ren, Long-Long; Zhou, En-Long; Qin, Yu-Feng (Frontiers in Chemistry, 2021)
Due to the high theoretical capability, copper-based oxides were widely investigated. A facile water bath method was used to synthesis CuO nanowires and CuO/Cu2O/Cu nanocomposites. Owing to the synergetic effect, the CuO/Cu2O/Cu nanocomposites exhibit superior electrochemical performance compared to the CuO nanowires. The initial discharge and charge capacities are 2,660.4 mAh/g and 2,107.8 mAh/g, and the reversible capacity is 1,265.7 mAh/g after 200 cycles at 200 mA/g. Moreover, the reversible capacity is 1,180 mAh/g at 800 mA/g and 1,750 mAh/g when back to 100 mA/g, indicating the excellent rate capability. The CuO/Cu2O/Cu nanocomposites also exhibit relatively high electric conductivity and lithium-ion diffusion coefficient, especially after cycling. For the energy storage mechanism, the capacitive controlled mechanism is predominance at the high scan rates, which is consistent with the excellent rate capability. The outstanding electrochemical performance of the CuO/Cu2O/Cu nanocomposites indicates the potential application of copper-based oxides nanomaterials in future lithium-ion batteries.